King Bhumibol Adulyadej’s Sufficiency Economy Philosophy and Post-Traumatic Stress Disorder among Higher-Education Students from the Armed Conflict Region of Thailand - Jatchavala, Chonnakarn; Vittayanont, Arnont (UI Scholars Hub, 2021)
This cross-sectional survey assessed the association between post-traumatic stress disorder symptoms and perceived self-sufficiency, reflecting the Sufficiency Economy Philosophy (SEP), conceived by H.M. King Bhumibol Adulyadej (King Rama IX). It was conducted among university students on one campus located within the area affected by the Southern Thailand insurgency and another campus located in a nearby province outside of the restive area. All self-administered questionnaires consisted of questions related to personal information, the Thai version of the PTSD checklist, and a questionnaire aimed at measuring the perceived self-sufficiency according to H.M. King Bhumibol Adulyadej’s SEP. The study found that most university students in the restive area affected by the Southern Thailand insurgency perceived to live sufficiently according to H.M. King Bhumibol Adulyadej’s SEP. The rate of perceived self-sufficiency was also higher than reported by the students from the other campus in a nearby province. Moreover, self-sufficiency exhibited a significant inverse association with PTSD symptoms.